2001
DOI: 10.1089/15246090152543166
|View full text |Cite
|
Sign up to set email alerts
|

Are the Physiologically and Psychosocially Based Symptoms in Women Suffering from Gynecological Disorders Alleviated by Means of Hysterectomy?

Abstract: Women experiencing gynecological disorders can suffer from a diversity of symptoms and problems. To what extent women are relieved of their physiologically and psychosocially based symptoms by hysterectomy is an important issue. This study aims to evaluate the long-term impact of hysterectomy on such symptoms and to compare the findings with those of a control group. Women with gynecological disorders experienced physiologically based symptoms, such as pelvic pain and urinary incontinence, to a greater degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
1
9
0
2
Order By: Relevance
“….informed consent is of critical importance because not only does this operation carry the operative morbidity and mortality that other surgical procedures have, but also alters the genital anatomy of the patient and in so doing may carry detrimental psychosexual consequences for some patientsQ (p. 41). To date, empirical evidence does not support any broad adverse effects of hysterectomy on women's psychosocial functioning [5]. Positive outcomes of hysterectomy include decreases in chronic pelvic pain and pain during intercourse, as well as the elimination of menstrual pain and dysfunctional uterine bleeding [21,23,54].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“….informed consent is of critical importance because not only does this operation carry the operative morbidity and mortality that other surgical procedures have, but also alters the genital anatomy of the patient and in so doing may carry detrimental psychosexual consequences for some patientsQ (p. 41). To date, empirical evidence does not support any broad adverse effects of hysterectomy on women's psychosocial functioning [5]. Positive outcomes of hysterectomy include decreases in chronic pelvic pain and pain during intercourse, as well as the elimination of menstrual pain and dysfunctional uterine bleeding [21,23,54].…”
Section: Discussionmentioning
confidence: 99%
“…The changes over the past decades in the psychological profile of patients may reflect a reduced tendency of health professionals to treat psychological and psychiatric symptoms with hysterectomy. Studies with control groups suggest no difference in psychological functioning between hysterectomy patients and controls [5,12,54]. Overall, there is no evidence that the uterus or its removal causes or relieves psychopathology (see Tables 1-4).…”
Section: Global Psychological Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross-sectional study, Ferroni and Deeble (1996) reported that women who had undergone hysterectomy for benign gynecological conditions reported less severe depressive symptomatology than women who had not received treatment for similar conditions. Rannestad et al (2001) found no differences in psychosocial well being among three groups: women with current gynecological illness, women who had previously undergone hysterectomy for similar conditions, and a healthy community sample. General life satisfaction among older women who had undergone hysterectomy was similar to or even higher than that among women of similar age who had never undergone hysterectomy (Kritz-Silverstein et al, 2002).…”
Section: Psychological Factorsmentioning
confidence: 73%
“…Rannestad et al, after carrying out a study of a group of women who had undergone gynaecological surgery procedures, paid attention to the increase in sleeping disorders presented by the respondents. Nonetheless, no changes of mental health (anxiety disorders or mental disorders) among those respondents were found [32]. On the other hand, according to the results obtained by Wang et al, who studied 105 Chinese women after hysterectomy, only 4.8% of these women were diagnosed with depression after the surgery [33].…”
Section: Discussionmentioning
confidence: 91%